Carrier Transport Properties of p-Type Silicon–Metal Silicide Nanocrystal Composite Films - Ohishi, Yuji; Miyazaki, Yoshinobu; Muta, Hiroaki; Kurosaki, Ken; Yamanaka, Shinsuke; Uchida, Noriyuki; Tada, Tetsuya (Journal of electronic materials, 2015)
In this study, we synthesized p -type nanocomposite films consisting of Si–nickel silicide and Si–molybdenum silicide nanocrystals and measured the temperature dependence of their electrical properties. To evaluate grain boundary potential barrier height, we developed a theoretical model taking into account the effect of ionized impurities, acoustic phonons, and grain boundaries. The potential barrier height was sufficiently low not to substantially affect carrier transport in the Si–nickel silicide composite film. Carrier transport in the Si–molybdenum silicide composite film was found to be affected by a scattering mechanism not included in this model. Thus, the transition metal significantly affects carrier transport and the thermoelectric properties of Si–metal silicide nanocomposite films.